The Sources of Chemical Contaminants in Food and Their Health Implications - Rather, Irfan A.; Koh, Wee Yin; Paek, Woon K.; Lim, Jeongheui (Frontiers in Pharmacology, 2017)
Food contamination is a matter of serious concern, as the high concentration of chemicals present in the edibles poses serious health risks. Protecting the public from the degrees of the harmfulness of contaminated foods has become a daunting task. This article highlights the causes, types, and health implications of chemical contamination in food. The food contamination could be due to naturally occurring contaminants in the environment or artificially introduced by the human. The phases of food processing, packaging, transportation, and storage are also significant contributors to food contamination. The implications of these chemical contaminants on human health are grave, ranging from mild gastroenteritis to fatal cases of hepatic, renal, and neurological syndromes. Although, the government regulates such chemicals in the eatables by prescribing minimum limits that are safe for human consumption yet measures still need to be taken to curb food contamination entirely. Therefore, a variety of food needs to be inspected and measured for the presence of chemical contaminants. The preventative measures pertaining about the food contaminants problems are pointed out and discussed.